Determinants of nurse ethical conduct in palliative care - Tomaszewska, Katarzyna; Majchrowicz, Bożena; Radoń, Katarzyna (Nursing in the 21st Century, 2022)
DETERMINANTS OF NURSE ETHICAL CONDUCT IN PALLIATIVE CAREIntroduction. The work of a nurse in palliative care creates the necessity to respect appropriate ethical directives in fulfi lling professional duties resulting from the need to protect patients’ basic values and rights.Aim. Assessing the determinants of nurse ethical behavior in palliative care.Material and methods. The study material was collected from 101 nurses working in the palliative care system. The study used the method of diagnostic survey by means of questionnaire technique. The research tool was the author’s survey questionnaire consisting of 26 questions. Non-parametric tests were used in data analysis: Pearson’s χ2 independence test, Mann-Whitney test and Kruskal-Wallis test. The signifi cance level of p